Epoxidized linolenic acid salts as multifunctional additives for the thermal stability of plasticized PVC. Issue 13 (10th December 2014) - Mohammed, Fiaz S.; Conley, Mark; Saunders, Steven R.; Switzer, Jackson; Jha, Rani; Cogen, Jeffrey M.; Chaudhary, Bharat I.; Pollet, Pamela; Eckert, Charles A.; Liotta, Charles L.
ABSTRACT Calcium and zinc salts of epoxidized linolenic acid were synthesized and used as multifunctional additives, to minimize or prevent the reaction of epoxidized soybean oil (ESO) with liberated hydrochloric acid (HCl) during the thermal degradation of poly(vinyl chloride) (PVC) in particular. These metal epoxy salts were incorporated as thermal stabilizers for both diisodecyl phthalate and ESO–plasticized PVC blends that underwent thermal degradation studies at 170°C. The overall performance of these metal epoxy salts was examined by thermal gravimetric analysis and visual color retention of the PVC blends. The weight loss profiles of the metal salt stabilized PVC were comparable to those of blends containing metal stearates. There were, however, vast improvements in color retention of the plasticized PVC using these novel additives. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41736.